OPTIMASI PENGGUNAAN SUMBERDAYA UNTUK MENCAPAI KEUNTUNGAN MAKSIMUM PADA USAHA MEUBEL âBAMBA RATTANâ DI KOTA PALU - Ferawati, Ferawati; Marhawati, Marhawati; Laapo, Alimuddin (AGROTEKBIS, 2016)
Â This study aims to know the amount of product which produced by âBamba Rattanâ furniture shop by using the available resources and to find out the maximum profit obtained âBamba Rattanâ furniture in Talise region, Palu. The research conducted on the âBamba Rattanâ furniture shop on July 2015 in Talise region, Palu. Respondents of this research of 4 people were business owner and 4 labors representative of âBamba Rattanâ furniture. The result showed that the number of products produced to obtain the maximum profit was 12 stels chair dining table and easy going desk chair 3 stels Â by using of the existing resources in the from of raw 95 kg materials, 243 laborsâ working day (HOK) and financial capital were Rp.12.471.135. Â Maximum profits by producing Chair Dinig Table and easy going desk chair were Rp.15.246.000.Â Key words : Bamba Rattan Furniture, Profits, Resource Optimization.